The first porphyrin–subphthalocyaninatoboron(iii)-fused hybrid with unique conformation and intramolecular charge transfer behavior. Issue 69 (5th August 2016) - Zhang, Yuehong; Oh, Juwon; Wang, Kang; Shin, Dongju; Zhan, Xiaopeng; Zheng, Yingting; Kim, Dongho; Jiang, Jianzhuang
Abstract : The first porphyrin–subphthalocyaninatoboron(iii )-fused hybrid with unique conformation and intramolecular charge-transfer behaviour has been isolated and structurally characterized. Abstract : Porphyrin and subphthalocyaninatoboron(iii ) chromophores have been fused through a quinoxaline moiety, resulting in the first porphyrin–subphthalocyaninatoboron(iii )-fused hybrid with intramolecular charge transfer from tetrapyrrole/tripyrrole chromophores to the quinoxaline moiety. The unique plane-bowl molecular structure of this hybrid was revealed based on single crystal X-ray diffraction analysis for the first time.